Entrepreneurial exploration and exploitation processes of family businesses in the food sector. Issue 11 (24th October 2019) - Vrontis, Demetris; Culasso, Francesca; Giacosa, Elisa; Stupino, Margherita
Abstract : Purpose: The purpose of this paper is to contribute to the entrepreneurship theory in family firms as it focuses on the relevance of an ambidextrous entrepreneurial strategy (Helfat and Peteraf, 2009 ), thanks to an effective combination between exploitation and exploration activities. The study refers to the food sector, characterized by established food traditions and changing consumption patterns. Design/methodology/approach: After reviewing the topics, the authors referred toGoel and Jones (2016) for its representativeness for the research. The authors conducted an explanatory case study in which the authors identified the framework's three sub-systems impacting the above family business systems. The case study is relevant because Eataly, a family-owned and -managed firm, is gaining recognition while applying a strong entrepreneurial strategy and it is unique in the world for the strength of its commercial strategy and dimensions. Findings: Entrepreneurship strategies can be explained by combined organizational antecedent conditions, represented by three sub-systems: family, business and ownership. The sub-systems' features and their interrelations play a relevant role in influencing entrepreneurial exploration and exploitation processes. Research limitations/implications: The study contributes to the actual entrepreneurship theory in family firms because it indicates the relevance of an ambidextrous entrepreneurial strategy, thanks to a combination of exploitation and exploration activities. In addition, it analyses the so-called antecedent conditions in organizations to achieve this favorable combination. Limitations involve the case study method and interview technique, both of which could be expanded. Practical implications: Several practical implications follow for different stakeholder categories (food sector companies, investors and private/public entities) concerning the management of antecedent conditions, the consequences of entrepreneurial investment policy, and tourism and territorial development. Originality/value: This research is novel because it combines an ambidextrous entrepreneurship approach (Goel and Jones, 2016 ) with the family firm's sub-systems (Tagiuri and Davis, 1982 ), observing how these sub-systems are relevant to defining and managing effective entrepreneurship strategy in a family food firm. The value added is particularly relevant in the food sector, which is characterized by low research and development. In addition, it requires innovative approaches to stimulate customers' perception of market demand, to satisfy their needs and to sustain family firms in a highly competitive environment.